The Colophon: Where moving parts come together - Meyle, Lucy; OHara, Emily; Redmond, Monique (Revista GEMInIS, 2022)
This article considers the colophon as a conceptual structure for thinking through lists and listing within creative practice(s). A colophon, typically found at the opening/end pages of a book, documents information about the publication production, its design characteristics and the context for which it was assembled. As artists practising in the inter-related fields of social, temporal and installation practices, we enjoy thinking about how the colophon might conceptually subvert and activate the working conditions within a project. This leads us to ask, how is this conception of the colophon useful in thinking about the other types of lists and listings that make their way into our collective practices? Contents, Captions, Legends, Work Lists, Indexes, Compilations. These particular modes of listing communicate relevant and intrinsic contexts and, in that way, become part of the conceptual life of artworks/projects. The Colophon: Where moving parts come together focuses on how the colophon can contribute meaning to social, object, material and temporal forms, thereby expanding the nature of engagement with artworks and events regarding the with who or the why here. Three perspectives will be discussed, exploring how the tropes of the colophon manifest as a potential system and tactical device in contemporary art.